Architectural Heritage of the Onega Gulf of the White Sea: the History of Study and Actual Problems of Research - Khodakovsky, Evgeny V.; Shcheglova, Yulia A. (Actual Problems of Theory and History of Art, 2022)
The article is devoted to the history of studying the architecture of the Onega Gulf of the White Sea. The description of the area is already found in travel notes of the 16th century, but the monuments of wooden architecture of this region were introduced into wide scientific circulation only in the late 1880s by academician V. V. Suslov. In addition, the historiography of the theme of wooden church architecture of the Onega Pomerania was accompanied by the research and publication of sources, on the basis of which their critical assessment was later based. So, the Archaeological Commission in 1911 published a list of churches in the Onega district in the “Description of monuments of Russian Architecture in the provinces”. The study of the architectural heritage of the Onega Seaboard was resumed only at the turn of the 1960s and 1970s, when the publications of I. B. Purishev, Yu. S. Ushakov, and M. I. Milchik were published almost simultaneously. Their articles and essays, along with materials published in the pre-revolutionary years, formed a solid basis for further scientific research in the 2010s, which presented the construction history and contextual analysis of temples in Unezhma, Purnema, Iur’eva Gora, Nimen’ga, Liamtsa, Pushlakhta and Letniaia Zolotitsa. On the basis of written sources (including unpublished materials of the Russian State Archive of Ancient Acts, the Moscow Kremlin Museums, the St. Petersburg Institute of History of the Russian Academy of Sciences) a significant body of archival primary sources on the history of wooden church building in the Onega Gulf of the White Sea, related to monastic clerical work, state accounting materials, documents of diocesan administration bodies, was identified. At the present stage, the main research approach can be called the expansion of the factual base due to, first, the introduction into scientific circulation of previously unknown documents clarifying the construction history of a particular object; secondly, the appeal to the restoration materials of the Soviet era, containing correspondence, drawings, projects and measurements of the 1950s and 1980s; thirdly, the series of expeditions, the results of which are detailed measurements of monuments and graphic reconstructions.The reported study was funded by RFBR, project number № 20-012-00356.
Keywords: Russian North; wooden architecture; historiography; White Sea; Pomors